2013
DOI: 10.1016/j.devcel.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol Synthesis Enzymes Mediate Lipid Droplet Growth by Relocalizing from the ER to Lipid Droplets

Abstract: SUMMARY Lipid droplets (LDs) store metabolic energy and membrane lipid precursors. With excess metabolic energy, cells synthesize triacylglycerol (TG) and form LDs that grow dramatically. It is unclear how TG synthesis relates to LD formation and growth. Here, we identify two LD subpopulations: smaller LDs of relatively constant size, and LDs that grow larger. The latter population contains isoenzymes for each step of TG synthesis. Glycerol-3-phosphate acyltransferase 4 (GPAT4), which catalyzes the first and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
781
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 688 publications
(832 citation statements)
references
References 55 publications
31
781
3
7
Order By: Relevance
“…The downregulation of the ER enzymes CDS1 or CDS2, which consume PA to form CDP-DAG, increases PA levels in the ER but also in LDs, an effect accompanied by LD enlargement and also observed with the downregulation of LIPIN1 [22]. The importance of PA in LD dynamics is highlighted by the localization of AGPAT3 and LIPIN1 in LDs [23,24], suggesting an in situ mechanism to control PA levels through its synthesis/degradation by these enzymes.…”
Section: The Er In Ld Biogenesis and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…The downregulation of the ER enzymes CDS1 or CDS2, which consume PA to form CDP-DAG, increases PA levels in the ER but also in LDs, an effect accompanied by LD enlargement and also observed with the downregulation of LIPIN1 [22]. The importance of PA in LD dynamics is highlighted by the localization of AGPAT3 and LIPIN1 in LDs [23,24], suggesting an in situ mechanism to control PA levels through its synthesis/degradation by these enzymes.…”
Section: The Er In Ld Biogenesis and Growthmentioning
confidence: 99%
“…LDs and ER could be directly connected by a continuity in their membranes [24,25], which would allow the transfer of lipids from the ER to support LD growth. In addition, these LD-ER connections could promote LD growth by facilitating the diffusion of lipogenic enzymes from the ER to increase in situ lipid synthesis [24,26].…”
Section: The Er In Ld Biogenesis and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…1,45 For example, Wifling et al identified LD populations that either remained static or expanded in response to oleic acid supplementation. 45 Furthermore, the expanding LD sub-population was characterized by glycerol-3-phosphate acyltransferase-4 co-localization, a rate limiting enzyme in triglyceride synthesis. 45 The ability to synthesize triglyceride directly at the LD surface may allow for rapid storage, thereby avoiding lipotoxicity.…”
Section: Tpd52 Functions At the Lipid Dropletmentioning
confidence: 99%
“…45 Furthermore, the expanding LD sub-population was characterized by glycerol-3-phosphate acyltransferase-4 co-localization, a rate limiting enzyme in triglyceride synthesis. 45 The ability to synthesize triglyceride directly at the LD surface may allow for rapid storage, thereby avoiding lipotoxicity. 45 Infrequent detection of TPD52 within the LD proteome 44 may also reflect that TPD52 associates with a subset of LDs within the cell, although a detailed analysis of TPD52 detection at LDs according to both size and responses to lipid loading will be required to determine whether this is true.…”
Section: Tpd52 Functions At the Lipid Dropletmentioning
confidence: 99%